2014
DOI: 10.1007/s12639-014-0595-3
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between Toxoplasma gondii infection and Parkinson’s disease: a case-control study

Abstract: Toxoplasma gondii is an obligate intracellular parasite that infects all nucleate cells of vertebrates. Human infected by vertical transmission and also using raw or undercooked meat or food and water that contaminated with mature oocysts. Parkinson's disease as neurodegenerative disease affects people above 60 years. Due to high prevalence of toxoplasmosis in Iran and evidence about effects of T. gondii on neurodegenerative diseases, this study has been conducted to investigate possible correlation between To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…26 Therefore, the results of our study do not support an association between T. gondii infection and Parkinson's disease. The lack of association between T. gondii infection and the presence of Parkinson's disease is consistent with similar results reported by Celik et al 14 15 and Oskouei et al 16 In contrast, our results conflict with those reported by Miman et al 13 who found a significantly higher seroprevalence of anti-T. gondii IgG antibodies in patients with Parkinson's disease than in controls. Other studies have also linked toxoplasmosis with Parkinson's disease.…”
Section: Discussionsupporting
confidence: 89%
“…26 Therefore, the results of our study do not support an association between T. gondii infection and Parkinson's disease. The lack of association between T. gondii infection and the presence of Parkinson's disease is consistent with similar results reported by Celik et al 14 15 and Oskouei et al 16 In contrast, our results conflict with those reported by Miman et al 13 who found a significantly higher seroprevalence of anti-T. gondii IgG antibodies in patients with Parkinson's disease than in controls. Other studies have also linked toxoplasmosis with Parkinson's disease.…”
Section: Discussionsupporting
confidence: 89%
“…Other neurodegenerative diseases have been investigated in different studies. For example, Mahami Oskouei et al implied no significant correlation between PD and toxoplasmosis (5). In this study, 85% of PD patients and 90.3% of controls were positive for anti-Toxoplasma IgG antibody.…”
Section: Discussionmentioning
confidence: 38%
“…Although T. gondii has affected nearly one-third of the world's population, the distribution of toxoplasmosis infection varies in different parts of the world (4). Previous studies showed a prevalence of 18 to 70% in different areas of Iran (5).…”
Section: Introductionmentioning
confidence: 99%
“…The association between T. gondii and dementia has been investigated in Parkinson's disease (PD), Alzheimer's disease (AD), and overall cognition. Several publications reported a positive correlation between PD and T. gondii seropositivity (83,84), although they were quickly followed by negative studies (85,86). In a recent meta-analysis on PD and T. gondii seropositivity, Zhou et al included seven studies with 1,086 subjects total and found no correlation between PD and T. gondii seropositivity (87).…”
Section: T Gondii and Humansmentioning
confidence: 99%